Preparation method of high-strength antibacterial packaging material

By using high-strength antibacterial packaging materials prepared by polylactic acid, nanocellulose and special antibacterial agents, the problems of poor antibacterial performance, low strength and small application range of existing packaging materials are solved, and efficient antibacterial performance and strength improvement are achieved, extending the shelf life and broadening the application range.

CN119842196APending Publication Date: 2025-04-18GUANGDONG ALICE PACKAGE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510053746.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing packaging materials have shortcomings in antibacterial properties, strength and scope of application, especially in humid environments, which are prone to bacteria and mold growth, and have limited strength and small scope of application.

Method used

Polylactic acid, nanocellulose, antibacterial agent, plasticizer and compatibility agent are used to prepare high-strength antibacterial packaging materials. The blend is formed and molded through a combined process of twin-screw extruder and blow molding machine. The antibacterial agent is prepared from tetrabutyl titanate, anhydrous ethanol, silver nitrate solution, deionized water and ammonia water to produce nanotitanium dioxide particles and silver ions, which have significant antibacterial properties.

Benefits of technology

It has achieved the preparation of high-strength antibacterial packaging materials, with significant antibacterial properties and strength, can effectively extend the shelf life of the product, and broaden the application range of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240749560000041
    Figure BDA0005240749560000041
  • Figure BDA0005240749560000051
    Figure BDA0005240749560000051
  • Figure BDA0005240749560000081
    Figure BDA0005240749560000081
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength antibacterial packaging material, particularly relates to the technical field of packaging materials, and relates to the preparation method of the high-strength antibacterial packaging material. The high-strength antibacterial packaging material is prepared from polylactic acid, nanocellulose, an antibacterial agent, a plasticizer and a compatilizer. The preparation method specifically comprises the following steps: treating polylactic acid, nano cellulose, an antibacterial agent, a plasticizer and a compatilizer, adding into a double-screw extruder, and mixing and extruding to obtain a blend; and molding the blend through a blow molding machine to obtain the high-strength antibacterial packaging material. The nano-crystalline cellulose is adopted to enhance the strength effect, the nano-crystalline cellulose has very high strength and modulus, the nano-size effect of the nano-crystalline cellulose enables the nano-crystalline cellulose to have relatively strong interaction with a polylactic acid molecular chain, and the nano-crystalline cellulose can bear and transfer externally applied stress, so that the mechanical properties such as tensile strength and tearing strength of the packaging material are improved; and the packaging material is not easy to break or damage under the action of external force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of packaging materials, and more specifically, to a method for preparing a high-strength antibacterial packaging material. Background Art

[0002] In the modern packaging industry, packaging materials must have good mechanical strength to protect the items in the package, prevent the product from physical damage, isolate the product from reacting with chemicals in the external environment, and effectively prevent microorganisms from invading the product; therefore, the development of a new packaging material is of great significance.

[0003] The packaging materials in the relevant technology mainly include low-density polyethylene, high-density polyethylene, polypropylene, and polyvinyl chloride; among them, polyethylene is soft, transparent, and waterproof, and is often used as a film for food packaging; high-density polyethylene has high hardness and strength, and is used to make plastic barrels and plastic bottles; polypropylene has low density, high strength, and good heat resistance, and is used to make food containers and tableware; polyvinyl chloride has good flexibility and chemical stability.

[0004] However, it still has some shortcomings in actual use, such as poor antibacterial performance. The packaging materials in the related technology have no antibacterial function and are prone to breed bacteria and mold in a humid environment, which will contaminate the products in the package; low strength. The molecular chain structure of the packaging materials in the related technology is relatively simple, and the interaction force between molecules is weak, resulting in limited overall strength; small scope of application. The packaging materials in the related technology are not suitable for specific types of products, storage and transportation conditions, which limits their scope of application. Summary of the invention

[0005] In order to improve the above problems and reduce the problems of poor antibacterial performance, low strength and small application range of traditional packaging materials, the present invention provides a method for preparing a high-strength antibacterial packaging material to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a high-strength antibacterial packaging material, which is prepared from polylactic acid, nanocellulose, an antibacterial agent, a plasticizer and a compatibilizer;

[0008] Specifically, polylactic acid, nanocellulose, antibacterial agent, plasticizer and compatibilizer are processed and then added into a twin-screw extruder for mixing and extrusion to obtain a blend; and the blend is then formed by a blow molding machine to obtain a high-strength antibacterial packaging material;

[0009] The antibacterial agent is prepared from tetrabutyl titanate, anhydrous ethanol, silver nitrate solution, deionized water and ammonia water;

[0010] Specifically, tetrabutyl titanate is first dissolved in anhydrous ethanol, a silver nitrate solution is added, and after stirring evenly, a mixed solution of deionized water and ammonia water is added dropwise, and then stirred for reaction. The generated precipitate is washed, dried, and calcined to obtain an antibacterial agent.

[0011] Preferably, the method for preparing the high-strength antibacterial packaging material comprises the following steps:

[0012] A1. Dry the polylactic acid in a vacuum drying oven at 50-80° C. for 2-4 hours to remove moisture and obtain dry polylactic acid;

[0013] A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1000-1500 r / min for 10-15 min to obtain dispersed nanocellulose;

[0014] A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, first stirring at a speed of 500-800 r / min for 8 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing stirring at a speed of 1000-1500 r / min for 15-20 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 100-150 r / min, and the temperature from the feeding section to the die head being 150-160° C., 160-170° C., 170-180° C., and 180-190° C., to obtain a blend;

[0015] A4. Add the blend obtained in A3 into a blow molding machine, and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

[0016] Preferably, the components and weight proportions of the raw materials for preparing the high-strength antibacterial packaging material are as follows:

[0017] Polylactic acid 65-80 parts, nanocellulose 12-20 parts, antibacterial agent 3-8 parts, plasticizer 5-10 parts and compatibilizer 2-5 parts

[0018] Preferably, the method for preparing the antibacterial agent comprises the following steps:

[0019] C1. Dissolve tetrabutyl titanate in anhydrous ethanol, stir on a magnetic stirrer at a stirring speed of 300-500 r / min until completely dissolved, then add a silver nitrate solution with a concentration of 0.1 mol / L, increase the stirring speed to 500-800 r / min, and stir for 30-60 min to form a mixed solution;

[0020] C2. Under the condition of stirring speed of 800-1200r / min, add a mixed solution of deionized water and 25-28% ammonia water into the mixed solution obtained in C1 at a dropping speed of 1-2ml / min. After the dropping is completed, place it in a constant temperature water bath at a temperature of 30-40°C, and react for 2-4 hours at a stirring speed of 600-800r / min to obtain a reaction solution.

[0021] C3. Transfer the reaction solution obtained in C2 to a centrifuge tube, centrifuge at a speed of 8000r / min for 10min, discard the supernatant, add 30ml of water, continue ultrasonic dispersion for 5min and then centrifuge again. Repeat this washing for 3 times, then put the washed precipitate into a vacuum drying oven, dry it at a temperature of 80-100℃ and a vacuum degree of (-0.08)-(-0.01)MPa for 12-24h, put the dried precipitate into a ceramic crucible, put it into a muffle furnace, heat it to 400-500℃ at a heating rate of 5-10℃ / min, and calcine it for 2-3h to obtain an antibacterial agent.

[0022] Preferably, the components and weight proportions of the raw materials for preparing the antibacterial agent are as follows:

[0023] 15-40 parts of tetrabutyl titanate, 60-180 parts of anhydrous ethanol, 3-12 parts of silver nitrate solution, 15-40 parts of deionized water and 3-12 parts of ammonia water.

[0024] Preferably, the plasticizer is glycerol.

[0025] Preferably, the compatibilizer is maleic anhydride grafted polylactic acid.

[0026] Technical effects and advantages of the present invention:

[0027] 1. The present invention uses tetrabutyl titanate, anhydrous ethanol, silver nitrate solution and ammonia water to prepare an antibacterial agent. When the nano titanium dioxide particles produced by the invention come into contact with bacteria, the silver ions therein can directly act on the bacteria, destroying the integrity of their cell walls and cell membranes, causing the cell contents to leak out, leading to bacterial death.

[0028] 2. The present invention uses nanocellulose to enhance strength. Nanocellulose has high strength and modulus. Its nanometer size effect enables it to have a strong interaction with the polylactic acid molecular chain, and can withstand and transmit externally applied stress, thereby improving the tensile strength, tear strength and other mechanical properties of the packaging material, making the packaging material less likely to break or be damaged when subjected to external forces;

[0029] 3. The present invention has extremely strong antibacterial properties and strength, can effectively prolong the shelf life of products, can prolong the shelf life of products, broaden the application scope of packaging materials, and can be effectively used in food, medical treatment, cosmetics, electronic products, and daily necessities. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the embodiments of the present invention. The raw materials used in the examples and embodiments of the present invention are all commercially available common materials unless otherwise specified below.

[0031] Preparation Example 1-5

[0032] An antibacterial agent, the preparation components and their corresponding proportions are shown in the following table, and is prepared by the following preparation method:

[0033] C1. Dissolve tetrabutyl titanate in anhydrous ethanol, stir on a magnetic stirrer at a stirring speed of 300 r / min until completely dissolved, then add a silver nitrate solution with a concentration of 0.1 mol / L, increase the stirring speed to 500 r / min, and stir for 30 min to form a mixed solution;

[0034] C2. Under the condition of stirring speed of 800r / min, a mixed solution of deionized water and 25% ammonia water is added dropwise into the mixed solution obtained in C1 at a dropping speed of 1ml / min. After the dropping is completed, it is placed in a constant temperature water bath at a temperature of 30°C and reacted for 2 hours under the condition of stirring speed of 600r / min to obtain a reaction solution.

[0035] C3. Transfer the reaction solution obtained in C2 to a centrifuge tube, centrifuge at a speed of 8000r / min for 10min, discard the supernatant, add 30ml of water, continue ultrasonic dispersion for 5min and then centrifuge again. Repeat this washing for 3 times, then put the washed precipitate into a vacuum drying oven, dry it at a temperature of 80℃ and a vacuum degree of -0.08MPa for 12h, put the dried precipitate into a ceramic crucible, put it into a muffle furnace, heat it to 400℃ at a heating rate of 5℃ / min, and calcine it for 2h to obtain an antibacterial agent.

[0036] Table: Components and volume ratios of raw materials in Preparation Examples 1-5 (ml)

[0037]

[0038]

[0039] Preparation Example 6

[0040] An antibacterial agent, which is different from Preparation Example 1 in that the preparation method is as follows:

[0041] C1. Dissolve tetrabutyl titanate in anhydrous ethanol, stir on a magnetic stirrer at a stirring speed of 350 r / min until completely dissolved, then add a silver nitrate solution with a concentration of 0.1 mol / L, increase the stirring speed to 550 r / min, and stir for 35 min to form a mixed solution;

[0042] C2. Under the condition of stirring speed of 900r / min, a mixed solution of deionized water and 26% ammonia water is added dropwise into the mixed solution obtained in C1 at a dropping speed of 1ml / min. After the dropping is completed, it is placed in a constant temperature water bath at a temperature of 32°C and reacted for 2.5 hours at a stirring speed of 600r / min to obtain a reaction solution.

[0043] C3. Transfer the reaction solution obtained in C2 to a centrifuge tube, centrifuge at a speed of 8000r / min for 10min, discard the supernatant, add 30ml of water, continue ultrasonic dispersion for 5min and then centrifuge again. Repeat this washing for 3 times, then put the washed precipitate into a vacuum drying oven, dry it at a temperature of 85℃ and a vacuum degree of -0.08MPa for 14.5h, put the dried precipitate into a ceramic crucible, put it into a muffle furnace, heat it to 420℃ at a heating rate of 6℃ / min, and calcine it for 2h to obtain an antibacterial agent.

[0044] Preparation Example 7

[0045] An antibacterial agent, which is different from Preparation Example 1 in that the preparation method is as follows:

[0046] C1. Dissolve tetrabutyl titanate in anhydrous ethanol, stir on a magnetic stirrer at a stirring speed of 400 r / min until completely dissolved, then add a silver nitrate solution with a concentration of 0.1 mol / L, increase the stirring speed to 600 r / min, and stir for 40 min to form a mixed solution;

[0047] C2. Under the condition of stirring speed of 950r / min, a mixed solution of deionized water and 26% ammonia water is added dropwise into the mixed solution obtained in C1 at a dropping speed of 1ml / min. After the dropping is completed, it is placed in a constant temperature water bath at a temperature of 34°C and reacted for 3 hours under the condition of stirring speed of 6500r / min to obtain a reaction solution.

[0048] C3. Transfer the reaction solution obtained in C2 to a centrifuge tube, centrifuge at a speed of 8000r / min for 10min, discard the supernatant, add 30ml of water, continue ultrasonic dispersion for 5min and then centrifuge again. Repeat this washing for 3 times, then put the washed precipitate into a vacuum drying oven, dry it at a temperature of 90℃ and a vacuum degree of -0.09MPa for 17h, put the dried precipitate into a ceramic crucible, put it into a muffle furnace, heat it to 440℃ at a heating rate of 7℃ / min, and calcine it for 2.5h to obtain an antibacterial agent.

[0049] Preparation Example 8

[0050] An antibacterial agent, which is different from Preparation Example 1 in that the preparation method is as follows:

[0051] C1. Dissolve tetrabutyl titanate in anhydrous ethanol, stir on a magnetic stirrer at a stirring speed of 450 r / min until completely dissolved, then add a silver nitrate solution with a concentration of 0.1 mol / L, increase the stirring speed to 700 r / min, and stir for 50 min to form a mixed solution;

[0052] C2. Under the condition of stirring speed of 1050r / min, a mixed solution of deionized water and 27% ammonia water is added dropwise into the mixed solution obtained in C1 at a dropping speed of 2ml / min. After the dropping is completed, it is placed in a constant temperature water bath at a temperature of 36°C and reacted for 3 hours at a stirring speed of 700r / min to obtain a reaction solution.

[0053] C3. Transfer the reaction solution obtained in C2 to a centrifuge tube, centrifuge at a speed of 8000r / min for 10min, discard the supernatant, add 30ml of water, continue ultrasonic dispersion for 5min and then centrifuge again. Repeat this washing for 3 times, then put the washed precipitate into a vacuum drying oven, dry it at a temperature of 90℃ and a vacuum degree of -0.09MPa for 19h, put the dried precipitate into a ceramic crucible, put it into a muffle furnace, heat it to 460℃ at a heating rate of 8℃ / min, and calcine it for 2.5h to obtain an antibacterial agent.

[0054] Preparation Example 9

[0055] An antibacterial agent, which is different from Preparation Example 1 in that the preparation method is as follows:

[0056] C1. Dissolve tetrabutyl titanate in anhydrous ethanol, stir on a magnetic stirrer at a stirring speed of 500 r / min until completely dissolved, then add a silver nitrate solution with a concentration of 0.1 mol / L, increase the stirring speed to 750 r / min, and stir for 55 min to form a mixed solution;

[0057] C2. Under the condition of stirring speed of 1100r / min, a mixed solution of deionized water and 27% ammonia water is added dropwise into the mixed solution obtained in C1 at a dropping speed of 2ml / min. After the dropping is completed, it is placed in a constant temperature water bath at a temperature of 38°C and reacted for 3.5 hours at a stirring speed of 750r / min to obtain a reaction solution.

[0058] C3. Transfer the reaction solution obtained in C2 to a centrifuge tube, centrifuge at a speed of 8000r / min for 10min, discard the supernatant, add 30ml of water, continue ultrasonic dispersion for 5min and then centrifuge again. Repeat this washing for 3 times, then put the washed precipitate into a vacuum drying oven, dry it at a temperature of 95℃ and a vacuum degree of -0.18MPa for 21.5h, put the dried precipitate into a ceramic crucible, put it into a muffle furnace, heat it to 480℃ at a heating rate of 9℃ / min, and calcine it for 3h to obtain an antibacterial agent.

[0059] Preparation Example 10

[0060] A high-strength antibacterial packaging material, which is different from Preparation Example 1 in that the preparation method is as follows:

[0061] C1. Dissolve tetrabutyl titanate in anhydrous ethanol, stir on a magnetic stirrer at a stirring speed of 500 r / min until completely dissolved, then add a silver nitrate solution with a concentration of 0.1 mol / L, increase the stirring speed to 800 r / min, and stir for 60 min to form a mixed solution;

[0062] C2. Under the condition of stirring speed of 1200r / min, a mixed solution of deionized water and 28% ammonia water is added dropwise into the mixed solution obtained in C1 at a dropping speed of 2ml / min. After the dropping is completed, it is placed in a constant temperature water bath at a temperature of 40°C and reacted for 4 hours under the condition of stirring speed of 800r / min to obtain a reaction solution.

[0063] C3. Transfer the reaction solution obtained in C2 to a centrifuge tube, centrifuge at a speed of 8000r / min for 10min, discard the supernatant, add 30ml of water, continue ultrasonic dispersion for 5min and then centrifuge again. Repeat this washing for 3 times, then put the washed precipitate into a vacuum drying oven, dry it at a temperature of 100℃ and a vacuum degree of -0.1MPa for 24h, put the dried precipitate into a ceramic crucible, put it into a muffle furnace, heat it to 500℃ at a heating rate of 10℃ / min, and calcine it for 3h to obtain an antibacterial agent.

[0064] Preparation Examples 11-15

[0065] A high-strength antibacterial packaging material, the preparation components and their corresponding proportions are shown in the following table, and is prepared by the following preparation method:

[0066] A1. Drying the polylactic acid in a vacuum drying oven at 50° C. for 2 h to remove moisture and obtain dry polylactic acid;

[0067] A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1000 r / min for 10 min to obtain dispersed nanocellulose;

[0068] A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, stirring at a speed of 500 r / min for 5 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing to stir at a speed of 1000 r / min for 15 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 100 r / min and a temperature of 150° C., 160° C., 170° C. and 180° C. from the feeding section to the die head, to obtain a blend;

[0069] The antibacterial agent is prepared by Preparation Example 1;

[0070] The plasticizer is glycerol;

[0071] The compatibilizer is maleic anhydride grafted polylactic acid;

[0072] A4. Add the blend obtained in A3 into a blow molding machine, and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

[0073] Table: Components and weight ratios of raw materials in Preparation Examples 11-15 (kg)

[0074]

[0075] Preparation Example 16

[0076] A high-strength antibacterial packaging material, which is different from Preparation Example 11 in that the preparation method is as follows:

[0077] A1. Drying the polylactic acid in a vacuum drying oven at 70° C. for 3 h to remove moisture and obtain dry polylactic acid;

[0078] A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1000 r / min for 10 min to obtain dispersed nanocellulose;

[0079] A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, stirring at a speed of 500 r / min for 5 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing to stir at a speed of 1000 r / min for 15 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 100 r / min and a temperature of 150° C., 160° C., 170° C. and 180° C. from the feeding section to the die head, to obtain a blend;

[0080] A4. Add the blend obtained in A3 into a blow molding machine, and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

[0081] Preparation Example 17

[0082] A high-strength antibacterial packaging material, which is different from Preparation Example 11 in that the preparation method is as follows:

[0083] A1, drying the polylactic acid in a vacuum drying oven at 80° C. for 4 h to remove moisture and obtain dry polylactic acid;

[0084] A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1000 r / min for 10 min to obtain dispersed nanocellulose;

[0085] A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, stirring at a speed of 500 r / min for 5 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing to stir at a speed of 1000 r / min for 15 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 100 r / min and a temperature of 150° C., 160° C., 170° C. and 180° C. from the feeding section to the die head, to obtain a blend;

[0086] A4. Add the blend obtained in A3 into a blow molding machine, and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

[0087] Preparation Example 18

[0088] A high-strength antibacterial packaging material, which is different from Preparation Example 11 in that the preparation method is as follows:

[0089] A1. Drying the polylactic acid in a vacuum drying oven at 50° C. for 2 h to remove moisture and obtain dry polylactic acid;

[0090] A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1250 r / min for 12.5 min to obtain dispersed nanocellulose;

[0091] A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, stirring at a speed of 500 r / min for 5 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing to stir at a speed of 1000 r / min for 15 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 100 r / min and a temperature of 150° C., 160° C., 170° C. and 180° C. from the feeding section to the die head, to obtain a blend;

[0092] A4. Add the blend obtained in A3 into a blow molding machine, and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

[0093] Preparation Example 19

[0094] A high-strength antibacterial packaging material, which is different from Preparation Example 11 in that the preparation method is as follows:

[0095] A1. Drying the polylactic acid in a vacuum drying oven at 50° C. for 2 h to remove moisture and obtain dry polylactic acid;

[0096] A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1500 r / min for 15 min to obtain dispersed nanocellulose;

[0097] A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, stirring at a speed of 500 r / min for 5 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing to stir at a speed of 1000 r / min for 15 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 100 r / min and a temperature of 150° C., 160° C., 170° C. and 180° C. from the feeding section to the die head, to obtain a blend;

[0098] A4. Add the blend obtained in A3 into a blow molding machine, and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

[0099] Preparation Example 20

[0100] A high-strength antibacterial packaging material, which is different from Preparation Example 11 in that the preparation method is as follows:

[0101] A1. Drying the polylactic acid in a vacuum drying oven at 50° C. for 2 h to remove moisture and obtain dry polylactic acid;

[0102] A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1000 r / min for 10 min to obtain dispersed nanocellulose;

[0103] A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, stirring at a speed of 650 r / min for 6.5 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing stirring at a speed of 1250 r / min for 17.5 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 125 r / min and a temperature of 150° C., 160° C., 170° C. and 180° C. from the feeding section to the die head, to obtain a blend;

[0104] A4. Add the blend obtained in A3 into a blow molding machine, and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

[0105] Preparation Example 21

[0106] A high-strength antibacterial packaging material, which is different from Preparation Example 11 in that the preparation method is as follows:

[0107] A1. Drying the polylactic acid in a vacuum drying oven at 70° C. for 3 h to remove moisture and obtain dry polylactic acid;

[0108] A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1000 r / min for 10 min to obtain dispersed nanocellulose;

[0109] A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, stirring at a speed of 500 r / min for 5 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing to stir at a speed of 1000 r / min for 15 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 100 r / min, and the temperature from the feeding section to the die head being 160° C., 170° C., 180° C. and 190° C. in sequence, to obtain a blend;

[0110] A4. Add the blend obtained in A3 into a blow molding machine, and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

[0111] Preparation Examples 22-30

[0112] A high-strength antibacterial packaging material, which is different from Preparation Example 11 in that the usage of the antibacterial agents used in its components is different, and the specific corresponding relationship is shown in the following table.

[0113] Table: Comparison of the use of antibacterial agents in Preparation Examples 22-30

[0114] Group Antimicrobial agents Preparation Example 22 Prepared from Preparation Example 2 Preparation Example 23 Prepared from Preparation Example 3 Preparation Example 24 Prepared by Preparation Example 4 Preparation Example 28 Prepared from Preparation Example 5 Preparation Example 26 Prepared from Preparation Example 6 Preparation Example 27 Prepared from Preparation Example 7 Preparation Example 28 Prepared from Preparation Example 8 Preparation Example 29 Prepared from Preparation Example 9 Preparation Example 30 Prepared from Preparation Example 10

[0115] Performance testing

[0116] The high-strength antibacterial packaging materials prepared in each embodiment were selected for testing, and the test objects were 200 portions of high-strength antibacterial packaging materials, 10 portions in each group; the antibacterial properties and strength thereof were tested, and the specific testing steps were as follows:

[0117] Antimicrobial:

[0118] First, the high-strength antibacterial packaging material prepared in the embodiment was sampled, cut into square pieces with a side length of 1 cm, and then placed on a 100 mL 10 6 CFU / ml E. coli suspension on the culture medium, then sample the E. coli colonies before and after 24 hours of culture, calculate the antibacterial rate of E. coli colonies before and after 24 hours of culture, and characterize the antibacterial properties of high-strength antibacterial packaging materials based on this data; the test results and evaluation criteria are as follows:

[0119] Antibacterial rate>90% (considered as strong antibacterial property);

[0120] 70%<antibacterial rate<90% (considered as general antibacterial property)

[0121] The antibacterial rate is less than 70% (considered as weak antibacterial activity).

[0122] strength:

[0123] First, the high-strength antibacterial packaging material prepared in the embodiment is sampled, and the tensile strength of the high-strength antibacterial packaging material is measured by a universal material test, and the moisture retention of the high-strength antibacterial packaging material is characterized based on this data; the test results and evaluation criteria are as follows:

[0124] Tensile strength>25MPa (considered as high strength);

[0125] Tensile strength <25MPa (considered as low strength);

[0126] It should be specifically noted that the high-strength antibacterial packaging material prepared above is a high-strength antibacterial packaging material produced in a normal production method, and the data of the defective high-strength antibacterial packaging material is discarded.

[0127] Examples 1-5

[0128] A high-strength antibacterial packaging material, and the corresponding relationship between the preparation methods used are shown in the following table.

[0129] Table: Comparison of usage of high-strength antibacterial packaging materials in Examples 1-5

[0130]

[0131]

[0132] The high-strength antibacterial packaging materials in the above Examples 1-5 were selected, and their antibacterial properties and strength were tested according to the above measurement steps and measurement standards. The average values ​​of the test results were recorded in the following table.

[0133] Table: Performance test results of Examples 1-5 for antibacterial properties and strength

[0134]

[0135] It can be seen from the above table that the high-strength antibacterial packaging material preparation process in Examples 1-5 has a good effect of improving the production effect of the high-strength antibacterial packaging material. The polylactic acid provides basic structural support for the material, and the nanocellulose is used to enhance the strength, improve the barrier performance, and stabilize the material structure; the antibacterial agent provides antibacterial protection, thereby achieving the purpose of improving the production effect of the high-strength antibacterial packaging material.

[0136] Its antibacterial rate is 90.1-92.3%, which is considered to be strong in antibacterial property; its tensile strength is 30.9-32MPa, which is considered to be high in strength;

[0137] It can be seen that when the production raw materials are certain, the production effect of the high-strength antibacterial packaging material can be increased by adjusting the proportion of the preparation raw materials. Combined with the data in the above table, it is not difficult to see that when preparing the high-strength antibacterial packaging material, when 80 parts of polylactic acid, 20 parts of nanocellulose, 8 parts of antibacterial agent, 10 parts of plasticizer, and 5 parts of compatibilizer are used, the antibacterial property and strength are the highest. The reason for this is that the content of the antibacterial agent is the highest, and there are more antibacterial components in the material that can play a role; at the same time, the higher content of polylactic acid and nanocellulose also provides a better dispersion carrier for nanosilver particles, which helps silver ions to better contact microorganisms, thereby showing the strongest antibacterial performance, and also significantly improves the strength of the material, so that the packaging material has better tensile resistance, impact resistance and other mechanical properties, as obtained by Examples 1-5.

[0138] Embodiment 6-11

[0139] A high-strength antibacterial packaging material, and the corresponding relationship between the preparation methods used are shown in the following table.

[0140] Table: Comparison of the use of high-strength antibacterial packaging materials in Examples 6-11

[0141] Group High-strength antibacterial packaging material Example 6 Prepared from Preparation Example 16 Example 7 Prepared from Preparation Example 17 Example 8 Prepared from Preparation Example 18 Example 9 Prepared from Preparation Example 19 Example 10 Prepared from Preparation Example 20 Embodiment 11 Prepared from Preparation Example 21

[0142] The high-strength antibacterial packaging materials in the above Examples 6-11 were selected, and their antibacterial properties and strength were tested according to the above measurement steps and measurement standards. The average values ​​of the test results were recorded in the following table.

[0143] Table: Performance test results of antibacterial properties and strength of Examples 1, 6-11

[0144]

[0145]

[0146] It can be seen from the above table that the high-strength antibacterial packaging material preparation process in Examples 6-11 has a good effect of improving the production effect of the high-strength antibacterial packaging material. The polylactic acid provides basic structural support for the material, and the nanocellulose is used to enhance the strength, improve the barrier properties, and stabilize the material structure; the antibacterial agent provides antibacterial protection, thereby achieving the purpose of improving the production effect of the high-strength antibacterial packaging material.

[0147] Its antibacterial rate is 90.5-91.2%, which is considered to be strong in antibacterial property; its tensile strength is 31.3-32.3MPa, which is considered to be high in strength;

[0148] It can be seen that when the production raw materials are constant, the production effect of the high-strength antibacterial packaging material can be increased by adjusting the preparation conditions. It is not difficult to see from the data in the above table that when the stirring speed and stirring time during the initial mixing in the preparation process of the high-strength antibacterial packaging material are increased; the stirring speed and stirring time during full mixing; the screw speed, temperature during extrusion granulation, and the temperature during extrusion, the antibacterial property and strength are also improved. The reason is that the stirring speed is accelerated and the time is extended in the initial mixing stage, which is conducive to a more uniform distribution of the antibacterial agent in the matrix material such as polylactic acid. The higher stirring speed and longer time in the full mixing stage can further refine the agglomerates of the antibacterial agent, so that it can be more evenly mixed with components such as nanocellulose, plasticizer and compatibilizer; prevent the antibacterial agent from agglomerating during the processing and losing part of its antibacterial activity. Increasing the screw speed in the extrusion granulation stage can increase the shear force of the material, so that raw materials such as polylactic acid and nanocellulose are better mixed and oriented at the molecular level; the increase in temperature is conducive to the uniform melting and extrusion of the material, and the defects inside the material are reduced, as obtained by Examples 1, 6-11.

[0149] Examples 12-15

[0150] A high-strength antibacterial packaging material, and the corresponding relationship between the preparation methods used are shown in the following table.

[0151] Table: Comparison of usage of high-strength antibacterial packaging materials in Examples 12-15

[0152] Group High-strength antibacterial packaging material Example 12 Prepared from Preparation Example 22 Embodiment 13 Prepared from Preparation Example 23 Embodiment 14 Prepared from Preparation Example 24 Embodiment 15 Prepared from Preparation Example 25

[0153] The high-strength antibacterial packaging materials in Examples 12-15 above were selected, and their antibacterial properties and strength were tested according to the above measurement steps and measurement standards. The average values ​​of the test results were recorded in the following table.

[0154] Table: Performance test results of antibacterial properties and strength of Examples 1, 12-15

[0155]

[0156] It can be seen from the above table that the high-strength antibacterial packaging material preparation process in Examples 1-5 has a good effect of improving the production effect of the high-strength antibacterial packaging material. The polylactic acid provides basic structural support for the material, and the nanocellulose is used to enhance the strength, improve the barrier performance, and stabilize the material structure; the antibacterial agent provides antibacterial protection, thereby achieving the purpose of improving the production effect of the high-strength antibacterial packaging material.

[0157] Its antibacterial rate is 90.5-91.4%, which is considered to be strong in antibacterial property; its tensile strength is 31.3-31.4MPa, which is considered to be high in strength;

[0158] It can be seen that when the production raw materials are certain, the production effect of high-strength antibacterial packaging materials can be increased by adjusting the preparation ratio of the antibacterial agent. Combined with the data in the above table, it is not difficult to see that when the raw material components of the antibacterial agent are increased, its antibacterial property is also improved. The reason for this is that the amount of silver nitrate solution determines the amount of silver ions introduced. More nano-titanium dioxide may provide more photocatalytic active sites and enhance the antibacterial performance, which is obtained from Examples 1 and 12-15.

[0159] Examples 16-20

[0160] A high-strength antibacterial packaging material, and the corresponding relationship between the preparation methods used are shown in the following table.

[0161] Table: Comparison of usage of high-strength antibacterial packaging materials in Examples 16-20

[0162] Group High-strength antibacterial packaging material Example 16 Prepared from Preparation Example 26 Embodiment 17 Prepared from Preparation Example 27 Embodiment 18 Prepared from Preparation Example 28 Embodiment 19 Prepared from Preparation Example 29 Embodiment 20 Prepared from Preparation Example 30

[0163] The high-strength antibacterial packaging materials in Examples 16-20 above were selected, and their antibacterial properties and strength were tested according to the above measurement steps and measurement standards. The average values ​​of the test results were recorded in the following table.

[0164] Table: Performance test results of antibacterial properties and strength of Examples 1, 16-20

[0165]

[0166] It can be seen from the above table that the high-strength antibacterial packaging material preparation process in Examples 16-20 has a good effect of improving the production effect of the high-strength antibacterial packaging material. The polylactic acid provides basic structural support for the material, and the nanocellulose is used to enhance the strength, improve the barrier performance, and stabilize the material structure; the antibacterial agent provides antibacterial protection, thereby achieving the purpose of improving the production effect of the high-strength antibacterial packaging material.

[0167] Its antibacterial rate is 90.5-91.4%, which is considered to be strong in antibacterial property; its tensile strength is 31.3-31.4MPa, which is considered to be high in strength;

[0168] It can be seen that when the production raw materials are certain, the production effect of high-strength antibacterial packaging materials can be increased by adjusting the preparation conditions of the antibacterial agent. Combined with the data in the above table, it is not difficult to see that when the stirring speed and time of the antibacterial agent process are increased; the stirring speed, dropping speed, temperature, and ammonia concentration of the hydrolysis reaction process; the centrifugal speed, time, and vacuum degree of the centrifugal process; the drying temperature, vacuum degree, and time of the drying process; the heating rate, temperature, and time of the calcination process are increased, the antibacterial property is improved. The reason for this is that increasing the stirring speed and time can make the raw materials mixed more evenly; sufficient stirring time and speed are conducive to the full hydrolysis and polycondensation reaction of tetrabutyl titanate to generate nano-titanium dioxide with smaller particle size and more uniform distribution; increasing the stirring speed can make the precipitate generated by the hydrolysis reaction more evenly dispersed in the reaction system In the process of preparing the reaction mixture, the supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 3 hours. The reaction mixture is stirred for 2 hours. The reaction mixture is stirred for 3 hours. The reaction mixture is stirred for 4 hours. The reaction mixture is stirred for 5 hours. The reaction mixture is stirred for 2 hours. The supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 3 hours. The supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 5 hours. The supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 3 hours. The supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 5 hours. The supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 2 hours. The supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 3 hours. The supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 3 hours. The supersaturation of the reaction mixture is increased, and the reaction mixture is stirred for 5 hours.

[0169] This specific embodiment is only an explanation of the present invention, not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of the claims of the present invention, it is protected by the patent law.

Claims

1. A method for preparing a high-strength antibacterial packaging material, characterized in that: The following steps are involved: A1. Dry the polylactic acid in a vacuum drying oven at 50-80° C. for 2-4 hours to remove moisture and obtain dry polylactic acid; A2, stirring the nanocellulose in a high-speed stirrer at a speed of 1000-1500 r / min for 10-15 min to obtain dispersed nanocellulose; A3, adding the dried polylactic acid obtained in A1 to a high-speed mixer, first stirring at a speed of 500-800 r / min for 8 min, then sequentially adding the dispersed nanocellulose, antibacterial agent, plasticizer and compatibilizer obtained in A2, continuing stirring at a speed of 1000-1500 r / min for 15-20 min, then adding to a twin-screw extruder, mixing and extruding at a screw speed of 100-150 r / min, and the temperature from the feeding section to the die head being 150-160° C., 160-170° C., 170-180° C., and 180-190° C., to obtain a blend; A4. Add the blend obtained in A3 into a blow molding machine and perform blow molding at a temperature of 180° C. and a pulling speed of 2.5 Hz to obtain a high-strength antibacterial packaging material.

2. The method for preparing a high-strength antibacterial packaging material according to claim 1, characterized in that: The components and weight proportions of the raw materials for preparing the high-strength antibacterial packaging material are as follows: 65-80 parts of polylactic acid, 12-20 parts of nanocellulose, 3-8 parts of antibacterial agent, 5-10 parts of plasticizer and 2-5 parts of compatibilizer.

3. The method for preparing a high-strength antibacterial packaging material according to claim 1, characterized in that: The antibacterial agent is prepared from tetrabutyl titanate, anhydrous ethanol, silver nitrate solution, deionized water and ammonia water.

4. The method for preparing a high-strength antibacterial packaging material according to claim 1, characterized in that: The preparation method of the antibacterial agent comprises the following steps: C1. Dissolve tetrabutyl titanate in anhydrous ethanol, stir on a magnetic stirrer at a stirring speed of 300-500 r / min until completely dissolved, then add a silver nitrate solution with a concentration of 0.1 mol / L, increase the stirring speed to 500-800 r / min, and stir for 30-60 min to form a mixed solution; C2. Under the condition of stirring speed of 800-1200r / min, add a mixed solution of deionized water and 25-28% ammonia water into the mixed solution obtained in C1 at a dropping speed of 1-2ml / min. After the dropping is completed, place it in a constant temperature water bath at a temperature of 30-40°C, and react for 2-4 hours at a stirring speed of 600-800r / min to obtain a reaction solution. C3. Transfer the reaction solution obtained in C2 to a centrifuge tube, centrifuge at a speed of 8000r / min for 10min, discard the supernatant, add 30ml of water, continue ultrasonic dispersion for 5min and then centrifuge again. Repeat this washing for 3 times, then put the washed precipitate into a vacuum drying oven, dry it at a temperature of 80-100℃ and a vacuum degree of (-0.08)-(-0.01)MPa for 12-24h, put the dried precipitate into a ceramic crucible, put it into a muffle furnace, heat it to 400-500℃ at a heating rate of 5-10℃ / min, and calcine it for 2-3h to obtain an antibacterial agent.

5. The method for preparing a high-strength antibacterial packaging material according to claim 1, characterized in that: The components and weight proportions of the raw materials for preparing the antibacterial agent are as follows: 15-40 parts of tetrabutyl titanate, 60-180 parts of anhydrous ethanol, 3-12 parts of silver nitrate solution, 15-40 parts of deionized water and 3-12 parts of ammonia water.

6. The method for preparing a high-strength antibacterial packaging material according to claim 1, characterized in that: The plasticizer is glycerol.

7. The method for preparing a high-strength antibacterial packaging material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polylactic acid.

Citation Information

Patent Citations

  • Method for preparing nano silver different in grain diameter

    CN103203466A

  • Preparation method for silver-containing titanium dioxide antibacterial agent

    CN108902177A

  • Preparation method and process of glass fiber / polylactic acid composite material

    CN111434716A

  • Biodegradable high-barrier-property antibacterial composite film and preparation method thereof

    CN113354853A

  • Degradable nanocellulose composite packaging material and preparation method thereof

    CN118725531A